ENGLISH FOR LAW: SEBUAH ANALISIS KEBUTUHAN BAHASA INGGRIS PADA MAHASISWA PROGRAM STUDI ILMU HUKUM FAKULTAS HUKUM USN KOLAKA - Rohima Nur Aziza Al Hakim (Jurnal Bahastra, 2018)
English is a General Basic Course which is taught in all majors including Law majors. English courses are intended for the development of skills and understanding of materials that are adapted to specific fields of study. But in the teaching process is still less effective because the content or the material being taught is not relevant to student majors. Therefore, it is necessary to apply English language teaching for a particular purpose (ESP) by conducting needs analysis based on the reasons and objectives for their learning English. By doing this the learner's needs can be met. Therefore this research was carried out with the aim; 1). To find out the problems faced by Law Study Program students in learning English; (2) To identify the needs of Law Study Program students in learning English related to English for Law material; This type of research is a qualitative research method, with a survey study design. This research was conducted at the Law Study Program at USN Kolaka. The object of this research is the Law Study Program students in the sixth semester of the 2019/2020 academic year who have programed the first English course in semester one and English II in the second semester. Data collection in this study was conducted by interview. The data analysis technique used in this research is descriptive qualitative. There are a number of things that become a problem in this ESP namely students who lack motivation and this course is considered difficult because of the factor of foreign language by these students. Need analysis which is important in this aspect of ESP includes some skills to support the career or work of future students, especially speaking and listening skills and also supported by reading and writing skills.